Influence of social media marketing on nutrition and physical activity behaviors of Romanian Generation Z students - Barna, Octavian; Musat, George Cosmin; Petcu, Damian; Georgescu, Adrian; Cazan, Florin; Georgescu, Andreea; Tanase-Popa, Daniela-Aurelia; Banu, Elena-Ariela (Progress in Nutrition, 2021)
A cross-sectional study was conducted on 1,284 students (18–25 y) including male and female students belonging to all the ages comprising the age group studied. Anthropometric measurements, i.e. height and weight were performed to calculate the body mass index (BMI). Social media (SM) usage, physical activity (PA), and nutrition behavior (NB) of the study’s subjects were assessed based on the student’s responses on a self-administered questionnaire. This questionnaire contained two sections: a section about the participants’ demographics and time spent on SM and another section that collected the participants’ views concerning the impact of SM advertisements (ads) on PA and NB. NB was assessed with the help of the Healthy Eating Index-2015 (HEI-2015) and PA was expressed in the metabolic equivalent (MET) of min/week. The subjects were divided into 3 categories in consideration of three possible responses to SM ads regarding nutrition and physical activity. These categories were: ignored, clicked and changed behavior. Two weeks after the initiation of the main study,  137 subjects including both male and female students was constituted to participate in an ancillary study. The students belonging to this sub-group were aged between 19–25 years and were randomly selected. Gender variations in SM usage were reported as the female students were found to be spending more time on SM platforms. Students who had a greater interest in diet ads on the SM platforms had higher HEI-2015 averaging 4.5 points (male) and 3.1 points (females) and lower BMI averaging 3.7 units (male) and 3.9 units (female) than those who ignored these ads. Increased PA of these students by 3,427.16 MET (male) and 3,307.53 MET (female) helped in reducing their BMI by 2.9 units (male) and by 2.8 units (female) was observed among the students with high interest in fitness programs promoted on SM.